Unified Power Quality Conditioner for voltage sag and harmonic mitigation of nonlinear loads - Y. Kusuma Latha; Ch. Saibabu; Y P Obulesu (Institute of Advanced Engineering and Science, 2011)
With the wide application of nonlinear and electronically switched devices in distribution systems, the power quality problem becomes more serious. This paper deals with Unified Power Quality Condition (UPQC) which is an integration of series active filter and shunt active filter. The main purpose of a UPQC is to compensate for current harmonics and voltage harmonics. It has the capability of improving power quality at the point of installation on power distribution systems. The paper discusses the compensation principle and different control strategies of the UPQC in detail. The performance of UPQC is examined by considering, a diode rectifier feeding an RL load (non linear load) that acts as a source of harmonics, feeding harmonics into the three-phase distribution system of concern. The performance is also observed under influence of utility side disturbances such as sag, swell, and flicker. This control strategy guarantees sinusoidal, balanced and minimized source currents even under unbalanced and / or distorted system voltages. The control strategies are modeled using MATLAB/SIMULINK and simulation results are presented to validate the proposed control strategy.Keywords—UPQC, Power Quality, Harmonics, Load Balancing, Power Factor Correction, MATLAB/SIMULINKDOI: http://dx.doi.org/10.11591/ijpeds.v1i1.35